THE SURFACE LAYER DISPLACEMENT OF THE CYLINDRICAL PARTS OF THE TRANSPORT PROCESSING TOOL MECHANISMS WITH FLEXIBLE WORK ITEMS - Kulichenko, O. Ya. (Science and Transport Progress, 2008)
In the article the relationships are determined between elastic-and-strained state of material, change of form and hardening of surface layer in the process of machining of metallic surface by instrument with flexible working elements. The results of tests are presented, which showed that the effect of hardening and the resistance to fatigue are rather high.